Способи одержання індивідуальних поліненасичених жирних кислот - Матвєєва, Тетяна Вікторівна (НТУ "ХПІ", 2015)
Поліненасичені жирні кислоти (ПНЖК) надзвичайно важливі для здоров’я людини. Організм людини не в змозі самостійно виробляти ці кислоти. Вони потрапляють до організму з їжею. Однак не завжди можна відкоригувати нестачу ПНЖК в організмі людини збалансованими харчовими продуктами. В статті здійснено аналіз науково-технічної інформації, щодо технологій одержання індивідуальних ПНЖК, зокрема арахідонової (АК), ейкозапентаєнової, -ліноленової, лінолевої та інших з доступної вітчизняної сировини з метою подальшого їх використання у харчовій, косметичній, фармацевтичній та хімічній галузях.

Polyunsaturated fatty acids (PUFA) are extremely important for human health. They have influence on growth forming and functioning of blood vessels, nervous system, development of glands, hydration of skin and general physical condition. Main PUFA are linoleic (w-6) linolenic (w-3) and derived from linoleic – arachidonic (w-6). Human body cannot produce these acids by itself. They are ingested to the body with food for instance with blended oils balanced according to fatty acid composition. However, lack of PUFA in human body not always can with be corrected with balanced nutrition. Scientific and technic information concerned technologies of individual fatty acids obtaining in particular arachidonic (AA) eicosapentaenoic, g- linolenic, linoleic and other acids for further utilization in food, cosmetic, pharmaceutical and chemical industry are presented in the article.
Methods of preparing individual polyunsaturated fatty acids
Keywords: арахідонова кислота; гідроліз; біоконверсія; трансформація; ПНЖК; АК; essential fatty acids; Mortierella alpine; arachidonic acid; hydrolysis; bioconversion